Using the Theory of Perceived Value to Determine the Willingness to Consume Foods from a Healthy Brand: The Role of Health Consciousness - Albornoz, Roger (2023)
Eating low amounts of healthy foods leads to high rates of diet-related diseases. How can we control and reduce the increase in these diseases? One of the recommendations is to improve nutritional competence, which means greater health consciousness. The objective of the present study is to determine the influence of health consciousness on the dimensions of perceived value and their impact on the willingness to consume foods from a healthy brand. Through a non-experimental, cross-sectional, and explanatory study, the responses of 518 participants (men and women) who confirmed being consumers of the healthy brands of food were analyzed. The study included adults aged from 18 to 58 years recruited using non-probability sampling. Data was collected using a self-report form and statistically analyzed using Smart PLS. The findings support that health awareness positively and significantly influences perceived quality value, perceived financial value, perceived social value, and perceived emotional value; contrary to this, it was detected that the perceived financial value does not influence the willingness to consume foods from healthy brands. This study contributes significantly to health science by showing how the theory of perceived value predicts the intention to consume healthy brands, with health consciousness intervening in this prediction. Therefore, it is concluded that the study population that consumes healthy foods has experienced the positive impact of perceived value and reports that the factors that comprise it influence their intention to consume healthy foods.